Uso do World Health Organization Disability Assessment Schedule para medir incapacidade em pacientes com DPOC ou insuficiência cardíaca: uma revisão sistemática - Medeiros, Roberta de Paiva (2023)
Introduction: Chronic obstructive pulmonary disease (COPD) and heart failure (HF) have similar symptoms and functional impairments, with consequent impairment of individuals' functioning. The World Health Organization Disability Assessment Schedule (WHODAS) is an instrument that has been used to assess functioning and disability in different disease populations. However, its use in these two diseases still seems to be very limited. Objective: To analyze how the WHODAS has been used in patients with COPD and/or HF, and what the scores are in these disease populations. Methods: A systematic literature review was carried out in electronic databases, including MEDLINE, EMBASE, Web of Science, CINAHL, PsycINFO, and LILACS from 1999 to October 2022. Two search strategies were constructed, one that included the keywords WHODAS and DPOC, and the other the keywords WHODAS and IC, both with their synonymous terms. We included articles that had used WHODAS in these disease populations, and we excluded review studies, studies in which COPD and/or HF did not have a confirmed diagnosis, in which individuals had a combination of diagnoses (eg, asthma and COPD), or studies that used the psychiatric version of the instrument. Data extraction was performed independently by two researchers and disagreements were solved by a third researcher. The extracted information was: characteristics of the studies; WHODAS application forms; and scores found (score by domain and total score). This review is registered in the PROSPERO database (registration number: CRD42022346355). Results: 14 publications with data from 11 studies were included. Most of these studies had a cross-sectional design (n=9) and were developed in South America (n=4) or Europe (n=4). In five of them, the WHODAS was used with individuals with COPD, in another five with individuals with HF, and in the same study, the instrument was used with both disease populations. Most studies used the 36-item version of the instrument (n=8) applied by interview (n=6). WHODAS measurement properties were investigated in COPD only. Of the studies that presented the summary score ranging from 0 to 100, the value ranged from 16.01 to 38.1 in individuals with COPD and from 14.7 to 38.4 in individuals with HF. The most compromised domains in individuals with COPD were “mobility” and “participation”, and “life activities” in individuals with HF. Conclusion: The use of the WHODAS questionnaire in people with COPD and HF still seems reduced and there is heterogeneity in its use. A preference for the 36-item version is suggested, as it allows scores per domain, and more studies should use the instrument before and after interventions.